Conceitos vagos ou indeterminados na fundamentação de decisões judiciais - Carvalho, Caio Augusto Nunes de (2018)
The present text addresses the comprehension of legal rules with vague semantic content in the judicial decision as the motivation content of these decisions, through a review of the legal literature and the humanities. Thus, the work deals with procedural and theoretical aspects of the motivation of judicial decisions, a topic that gains prominence within the Constitutional rule of law and the theory of law, in order to generate controllability of court actions and legitimacy of jurisdiction. As a result, it provides a contribution to the understanding of the current meaning of the dimensions of motivation when these vague semantic terms are present, as well as a contribution to the understanding of the reasoning interaction with other legal aspects of the civil procedure and constitutional rights and guarantees